Engaging with Public Opinion at the Micro-Level: Citizen Dialogue and Participation in German Foreign Policy. Issue 1 (19th October 2021) - Opitz, Christian; Pfeifer, Hanna; Geis, Anna
Abstract: This article analyzes how and why foreign policy (FP)-makers use dialogue and participation processes (DPPs) with (groups of) individual citizens as a source of public opinion. Taking Germany as a case study and drawing on DPP initiatives by the Federal Foreign Office ( Auswärtiges Amt, AA) since 2014, we analyze the officials' motivation for establishing such processes and find four different sets of motivation: (1) image campaigning, (2) educating citizens, (3) listening to citizens, and (4) changing the citizens' role in FP. Our article makes three contributions. First, we provide a novel typology of the sources of public opinion upon which FP-makers can draw. Second, our study points to the importance of, and provides a framework for, analyzing how officials engage with public opinion at the micro-level, which has so far been understudied in FP analysis. Finally, our empirical analysis suggests that both carefully assessing and influencing public opinion feature prominently in motivation, whereas PR purposes are of minor importance. Recasting the citizens' role in FP gains in importance over time and may mirror the increased need to legitimize FP in Western democracies vis-à-vis their publics.